Sosialisasi Kegiatan Bimbingan Gratis Bagi Siswa UPTD SD Negeri 122358 Pematang Siantar - Selviana Napitupulu; Jumaria Sirait; Susy Alestriani Sibagariang; David Berthony Manalu; Injen Pardamean Butar-Butar; Osco Parmonangan Sijabat (Society : Jurnal Pengabdian Masyarakat, 2023)
Socialization of free tutoring activities is one of the efforts to accelerate the education acceleration program so that national education goals can be achieved. The socialization of this free tutoring activity was carried out by a team of volunteers from University of HKBP Nommensen Pematangsiantar with students at the elementary level located at UPTD SD Negeri 122358 Pematang Siantar. The purpose of this activity is to find out problems related to learning after the Covid-19 pandemic and the impact if character-based thematic learning programs with free tutoring are implemented. From the results of this training activity it was known that the enthusiasm of the students was very pleasant because they received free tutoring that they had never enjoyed before. This activity develops student motivation at school. The biggest hope of the students and teachers and leaders at the school is that this activity program can be sustainable so that it can help students.